2021
DOI: 10.1080/10717544.2021.1955042
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and use of nanogels as carriers of drugs

Abstract: Nanogels have high tunability and stability while being able to sense and respond to external stimuli by showing changes in the gel volume, water content, colloidal stability, mechanical strength, and other physical/chemical properties. In this article, advances in the preparation of nanogels will be reviewed. The application potential of nanogels in drug delivery will also be highlighted. It is the objective of this article to present a snapshot of the recent knowledge of nanogel preparation and application f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 101 publications
0
48
0
1
Order By: Relevance
“…Moreover, it has a tendency to retain a large quantity of aqueous fluid without dissolving onto them and is widely explored in drug delivery and biomedical engineering. The polymeric network in the gel system plays a significant role in determining physicochemical properties and hydrophilicity, and controlling particle size; small pores in the polymeric network enables the accommodation of small molecules [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has a tendency to retain a large quantity of aqueous fluid without dissolving onto them and is widely explored in drug delivery and biomedical engineering. The polymeric network in the gel system plays a significant role in determining physicochemical properties and hydrophilicity, and controlling particle size; small pores in the polymeric network enables the accommodation of small molecules [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As NPs possess an ability to load and deliver an amazing spectrum of drugs to almost any organ of the body, delivering focused, regulated, as well as prolonged therapeutic effects, they have become an important subject of drug delivery studies [ 12 ] as shown in Table 1 . Examples of nanogels are reported for drug delivery applications including both hydrophobic and hydrophilic agents, and even oligodeoxynucleotides [ 13 ].…”
Section: Nanocarrier As a Drug Delivery Mechanismmentioning
confidence: 99%
“…Nanogels are employed for both local and systemic drug action because of their natural ability to swell due to chemical alteration, allowing the drug to be released in the desired dosage form [ 13 ]. Nanogels can be used to make dermal patches, biosensors, and ionic drug delivery.…”
Section: Nanotechnological Approachmentioning
confidence: 99%
“…Various fabrication methods for these nanoparticles have been developed to match the used material to properties of the encapsulated cargo and its intended target. Extensive reviews summarizing these methods are available in the literature [29][30][31][32][33]. Nanoparticles, whether lipid or polymeric, typically show a particle size range of 1 to 100 nm [34], though some use the term for larger particles, up to 500 nm.…”
Section: Nanoparticlesmentioning
confidence: 99%